1999
DOI: 10.1159/000016568
|View full text |Cite
|
Sign up to set email alerts
|

Microradiographic and Microscopic Studies on in situ Induced Initial Caries in Irradiated and Nonirradiated Dental Enamel

Abstract: The objective of this study was to evaluate the onset of initial demineralization in irradiated and nonirradiated human enamel. Enamel specimens were prepared from the lingual and buccal surfaces of 48 freshly extracted, caries–free third molars. Either the lingual or the buccal enamel specimen of each tooth was irradiated with 60 Gy. The remaining enamel sample was not irradiated. Two irradiated and two nonirradiated enamel specimens were inserted into both buccal aspects of each 12 intraoral mandibular appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
2
35
1
14
Order By: Relevance
“…On the other hand, in studies using powdered enamel or apatite an increased solubility of irradiated, human enamel has also been reported [Pioch et al, 1991;Tepel et al, 1992]. Nevertheless, in situ investigations using TMR [Kielbassa et al, 1997b[Kielbassa et al, , 2000 seem to be more reliable to measure the outcome of irradiation. Thus, in light of the present data it seems very likely that irradiation does not infl uence demineralization of human enamel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in studies using powdered enamel or apatite an increased solubility of irradiated, human enamel has also been reported [Pioch et al, 1991;Tepel et al, 1992]. Nevertheless, in situ investigations using TMR [Kielbassa et al, 1997b[Kielbassa et al, , 2000 seem to be more reliable to measure the outcome of irradiation. Thus, in light of the present data it seems very likely that irradiation does not infl uence demineralization of human enamel.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was observed in an in situ demineralization model that irradiated human enamel is as caries susceptible as nonirradiated. It was concluded that possible irradiation effects are not likely to be responsible for initial demineralization under clinical conditions [Kielbassa et al, 2000]. …”
mentioning
confidence: 99%
“…Studies on the mechanical properties of irradiated teeth are often hampered by "nonphysiological" conditions, such as the application of mechanical forces that exceeded the elastic limit of the samples 2,3) . Nonetheless, radiation caries seems to originate from radiation-induced defects in the amelodentinal junction and changes in the oral flora [4][5][6] due to reduced salivary flow rate and poor oral hygiene 7) . Besides irradiation-induced xerostomia, the effect of irradiation on dental hard tissues may be an important factor in radiation caries.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,24,25,26,27 However, only limited information is available concerning these effects on both enamel and dentine. Moreover, most of the previous investigations had limitations with regard to the instruments used, and there has been little study concerning the relationship between radiation dose and mechanical properties.…”
Section: Discussionmentioning
confidence: 99%